Impact of COVID-19 on cardiovascular diseases: experience at a teaching hospital from rural Telangana - Jain, Archana Santosh; Khedkar, Swaralee; Jangala, Madhavi (International Journal Of Community Medicine And Public Health, 2022)
Background: COVID-19 is drastically affecting the health of millions of people globally. Further, the restrictions imposed during lockdowns to curtail the spread of COVID-19 have also shown impact on the economy, psychology and lifestyle of the people. However, little is known about the prevalence and clinical manifestations of COVID-19 in coronary heart diseases in rural India. Hence, the present study aimed to find the effect of COVID-19 and lockdown on the prevalence of coronary heart diseases in rural Telangana. Methods: The present retrospective study was carried on 1320 medical reports of cardiac inpatients who visited RVM Institute of Medical Sciences and Research Center, Siddipet, Telangana during the period 17th January 2020 to 6th August 2020. The data obtained was analyzed by descriptive statistics using IBM SPSS Statistics version 21.0. Results: Admission of patients with STEMI (53.6% prelockdown; 26% lockdown period; 36.4% post lockdown) and arrhythmia (7.3% prelockdown; 1.3% post lockdown) decreased while there was a significant increase in hospitalization of myopericarditis patients (1% pre lockdown vs. 10.5% lock down, 9.2% post lockdown) after the initiation of lockdown period. Further, STEMI (mean age 42.07±15.06) and myopericarditis (mean age 30.8±9.02 years) was commonly seen in younger age group patients less than 45 years after the initiation of lockdown period. The mortality rate was 6.6% (n=13) in the total study period of which 57.5% (n=7) deaths were due to myocardial infarction. 63.6% of the cardiac patients tested by RT-PCR were found to be positive for COVID-19. Conclusions: The prevalence of cardiovascular diseases varied with lockdown periods. Young adults in rural Telangana were also affected by COVID-19 and lockdown.